Cultivating Discipline and Responsibility Character Through the Tahfidz Program - Firdausiyah, Annisa Putri; Az Zafi, Ashif (Jurnal Pendidikan Islam, 2026)
Islamic boarding schools aim to cultivate generations that are academically competent and morally virtuous. The Qur'an Tahfidz program at Pondok Pesantren Yanabiul Ulum Warrahmah (PPYUR) extends beyond mere memorization to instill values of discipline and responsibility. The second-grade Tahfidz class represents a critical phase where these values begin to be systematically formed, warranting further investigation. This study seeks to describe and analyze the process of embedding discipline and responsibility values, while examining their impact on second-grade students at Pondok Pesantren Yanabiul Ulum Warrahmah (PPYUR). Utilizing a qualitative case study approach, data was gathered through participant observation, interviews with instructors and students, and document analysis. The data underwent interactive analysis involving reduction, presentation, and verification to ensure validity. The findings demonstrate the program's effectiveness in fostering discipline and responsibility through structured routines including daily memorization targets, muroja'ah, sima'an (recitation assessment), and a partnership system. The instructors' role as direct mentors and exemplars proved pivotal to this success. This research is expected to serve as an evaluative resource for enhancing the integration of Tahfidz programs with character education in Islamic boarding schools.